20.1k views
0 votes
I've included two questions. Hopefully you can help me with both. Thanks!

I've included two questions. Hopefully you can help me with both. Thanks!-example-1
I've included two questions. Hopefully you can help me with both. Thanks!-example-1
I've included two questions. Hopefully you can help me with both. Thanks!-example-2
User Ppearcy
by
4.9k points

1 Answer

2 votes

Answer:

1. value is 0; x-3 is a factor . . . . . . . . . . . . . .third choice

2. evaluates at x = -1; remainder is -11 . . . . first choice

Explanation:

Dividing f(x) by (x -a) gives ...

f(x)/(x -a) = g(x) +r/(x -a) . . . . some quotient and a remainder r

If we multiply this expression by (x -a), we see ...

f(x) = (x -a)g(x) +r

so

f(a) = (a -a)g(a) +r . . . . . evaluate the above equation at x=a

f(a) = 0 +r

f(a) = r . . . . . . . . . a statement of the remainder theorem

If r=0, then x-a is a factor of f(x) = (x-a)g(x).

___

1. We have "a" = 3, and f(3) = 0. Therefore (x-3) is a factor.

__

2. We have "a" = -1, and f(-1) = -11. Therefore the remainder from division by (x+1) is -11.

I've included two questions. Hopefully you can help me with both. Thanks!-example-1
User ViToni
by
5.5k points